A Study of the Reaction Product of Factor VIII and Factor IX by Gel Filtration - Hougie, C; Denson, K. W. E; Biggs, Rosemary (Thrombosis and Haemostasis, 1967)
The products of the reaction of activated factor IX with factor VIII, phospholipid and calcium have been studied using gel filtration on Sephadex G-200. Both factor VIII and phospholipid are completely excluded from the gel (distribution coefficient or KD of zero) while factor IXa behaves like a protein similar in size to albumin (KD approx. 0.4). Factor IXa complexes with phospholipid when calcium ions are added to the eluting buffer. When factor VIII, factor IXa, phospholipid and calcium are applied to the column and eluted with added Ca++ in the eluting buffer, a labile product with a KD of 0 is formed. The product apparently dissociates in the absence of added calcium ions in the eluting buffer. In the presence of calcium ions, the distribution coefficient of factor IX, when applied alone to the column, increased. The above findings are analogous to those reported between activated factor X, thrombin-activated factor V, phospholipid and calcium occurring later in the coagulation process.